1990
DOI: 10.20506/rst.9.4.534
|View full text |Cite
|
Sign up to set email alerts
|

A new leptospiral serovar in the Pyrogenes serogroupe isolated in Nigeria

Abstract: Five leptospiral strains were isolated from bovine kidneys during a cultural survey for pathogenic leptospires in Nigeria. Preliminary test results indicated that the five strains were identical and serologically heterologous to the other members of the Pyrogenes serogroup. Further examination of the strains by the cross-agglutinin absorption test, factor analysis and restriction endonuclease analysis confirmed that the strains constitute a new serovar. It is therefore proposed that this strain be recognised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…infection was demonstrated in a wide range of animal hosts ( S1 Table ), including cattle ( Bos spp.) [ 85 , 87 , 89 91 , 93 – 102 , 111 , 114 , 119 , 121 , 127 ]; pigs ( Sus scrofa domestica ) [ 78 , 79 , 84 , 85 , 100 , 104 , 106 , 122 ]; goats ( Capra aegagrus hircus ) [ 85 ]; Rusa deer ( Rusa timorensis ) [ 85 ]; dogs ( Canis lupis familiaris ) [ 85 , 113 , 116 ]; cats ( Felis catus ) [ 85 , 113 , 116 ]; rodents including the African grass rat ( Arvicanthus niloticus ) [ 87 , 88 ], African giant pouched rat ( Cricetomys gambianus ) [ 110 , 112 ], lesser tufted-tailed rat ( Eliurus minor ) [ 125 ], fringe-tailed Gerbil ( Gerbilliscus robustus ) [ 77 , 88 ], rusty-bellied brush-furred rat ( Lophuromus sikapusi ) [ 109 ], multimammate mouse ( Mastomys sp.) [ 83 , 87 , 103 , 115 ], house mouse ( Mus musculus ) [ 80 , 81 , 83 , 85 , 118 ,…”
Section: Resultsmentioning
confidence: 99%
“…infection was demonstrated in a wide range of animal hosts ( S1 Table ), including cattle ( Bos spp.) [ 85 , 87 , 89 91 , 93 – 102 , 111 , 114 , 119 , 121 , 127 ]; pigs ( Sus scrofa domestica ) [ 78 , 79 , 84 , 85 , 100 , 104 , 106 , 122 ]; goats ( Capra aegagrus hircus ) [ 85 ]; Rusa deer ( Rusa timorensis ) [ 85 ]; dogs ( Canis lupis familiaris ) [ 85 , 113 , 116 ]; cats ( Felis catus ) [ 85 , 113 , 116 ]; rodents including the African grass rat ( Arvicanthus niloticus ) [ 87 , 88 ], African giant pouched rat ( Cricetomys gambianus ) [ 110 , 112 ], lesser tufted-tailed rat ( Eliurus minor ) [ 125 ], fringe-tailed Gerbil ( Gerbilliscus robustus ) [ 77 , 88 ], rusty-bellied brush-furred rat ( Lophuromus sikapusi ) [ 109 ], multimammate mouse ( Mastomys sp.) [ 83 , 87 , 103 , 115 ], house mouse ( Mus musculus ) [ 80 , 81 , 83 , 85 , 118 ,…”
Section: Resultsmentioning
confidence: 99%
“…An overall seroprevalence of 19% implies exposure of cattle to leptospires, with sv Pomona making the largest contribution, followed by sv Kenya and Nigeria. Cattle are known to be maintenance hosts for sv Pomona [ 19 ] and possibly Nigeria [ 5 ] elsewhere. It is therefore possible that the seropositive cattle were not only exposed to leptospires in the past, but also function as maintenance hosts, likely exposing humans and other species by direct urine splashes or by shedding leptospires in water and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…A serological survey found that 35% (126/359) of humans visiting two health centers in Western Uganda had antibodies against leptospiral serovars and 2% had antibody titers corresponding with probable recent leptospirosis when tested by the Microscopic Agglutination test (MAT). The most common serovar was Leptospira (L.) borgpetersenii sv Nigeria (sg Pyrogenes) with 19.8%, which had been isolated from bovines elsewhere in Africa [ 5 ]. Another prevalent sg in these patients was Sejroe represented by sv Hardjobovis and sv Wolffii with 5.6% and 5.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We further detected a seroprevalence of 20% against sv Nigeria sg Pyrogenes, which was the most frequent serovar or serogroup for exposure. Historically, sv Nigeria was isolated from bovine kidneys in Nigeria [ 21 ]. The high prevalence of antibodies against sv Nigeria raises concern for a bovine-human transmission pathway in western rural Uganda that deserves further examination.…”
Section: Discussionmentioning
confidence: 99%